The Serum Damine oxidase (DAO), serum bacterial endotoxin (BT) and D-lactic acid (D-Lac) TNF-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) in patients sepsis combined with acute kidney injury after Bexira administration: Serum biomarkers in patients with sepsis - Huang, Handong (Journal of Medical Biochemistry, 2025)
Objective: The present investigations were designed to investigate the clinical effectiveness of Bexira in acute kidney injury patients complicated by a septic condition, and further analyze its potential effects on Serum Damine oxidase (DAO), serum bacterial endotoxin (BT) and D-lactic acid (D-Lac) TNF-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) in patients, so as to enhance the scientific basis for clinical treatments. Methods: Between January 2024 and December 2024, 200 patients with sepsis associated with acute kidney injury were admitted to our hospital. These individuals were incorporated into our research cohort. In order to ensure the scientificity and comparability of the study, we used A random number table method to randomly divide these 200 patients into panels A and B, with 100 patients in per group. Group A patients received standard conventional care, including but not limited to anti-infective therapy, nutritional support, and symptomatic management. Group B received additional treatment with Bexira on the basis of group A. All patients enrolled in the study underwent detailed clinical assessments and appropriate medical examinations to ensure the safety and efficacy of the treatment. Prior to treatment, all patients underwent a comprehensive assessment to understand their baseline health status. 7 days after the start of treatment, the changes of intestinal mucosal barrier function, immune function and their prognosis were monitored in both groups. By comparing the two populations before and after treatment, we aim to better understand what factors may affect a patient’s recovery process and long-term prognosis. Results: After 7 days of treatment, we observed significant reductions in diamine oxidase (DAO) levels, bacterial endotoxin (BT) content, and D-lactic acid (D-Lac) concentration in both experimental groups. Especially in group B, the changes of these three biomarkers were more significant, and their values were lower than those of control group A, indicating that the treatment effect of group B was better than that of group A. This variation is of major concern in terms of statistically validity, that is, P<0.05, meaning that the test results could not be regarded as due to chance or error, but could be confirmed as changes in biological indicators caused by effective treatment strategies. These data not only demonstrate the short-term effect of the treatment, but also hint at possible long-term benefits, and warrant further research to explore more about the pharmacological mechanism of effect and clinical application of this agent. Conclusions: Among the many options for treating sepsis associated with acute kidney injury, the application of Bexira proved to be a significant advance. also enhance the level of the body’s immune response, thereby helping to improve the overall health status and prognosis of patients.